An ILS-based algorithm to solve a large-scale real heterogeneous fleet VRP with multi-trips and docking constraints. - Coelho, Vitor Nazário (2016)
Distribution planning is crucial for most companies since goods are rarely produced and consumed at the same place. Distribution costs, inaddition, can be an important component of the final cost of the products. In this paper, westudya VRP variant inspired on a real case of a large distribution company. In particular, we consider a VRP with a heterogeneous fleet of vehicles that a real lowed to perform multipletrips. The problem also includes docking constraints in which some vehicles are unable to serve some particular customers, and a realistic objective function with vehicles’ fixed and distance- based costs and a costper customer visited. We design a trajectory search heuristic called GILS-VND that combines Iterated Local Search (ILS), Greedy Randomized Adaptive Search Procedure (GRASP) and Variable Neighborhood Descent (VND) procedures. This method obtains competitive solutions and improves the company solutions leading to significant savings in transportation costs.